2020
DOI: 10.1002/ceat.201900199
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Methyl Chloride on Molecular Sieves, Silica Gels, and Activated Carbon

Abstract: Adsorption of methyl chloride (CH3Cl or MeCl) on five different types of adsorbents was investigated experimentally at increasing pressures and room temperature. Prior to adsorption, all adsorbents were analyzed to assess their physical and chemical characteristics. The experimental data was then used to determine the adsorption isotherms, heats of adsorption, adsorption rates, and their respective theoretical models. The MeCl adsorption capacity was found to reasonably correlate with the adsorbent's surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…PFO gave an insight that the rate-limiting step involved in the adsorption of RBBR onto LSDAC was contributed by physisorption. A similar case was observed in methyl chloride adsorption by AC . Rate constants from both PFO and PSO were found to decrease from 0.0215 to 0.0122 min –1 and from 0.00094 to 0.00004 g mg –1 min –1 , respectively, as the initial concentration of RBBR increased from 25 to 300 mg/L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PFO gave an insight that the rate-limiting step involved in the adsorption of RBBR onto LSDAC was contributed by physisorption. A similar case was observed in methyl chloride adsorption by AC . Rate constants from both PFO and PSO were found to decrease from 0.0215 to 0.0122 min –1 and from 0.00094 to 0.00004 g mg –1 min –1 , respectively, as the initial concentration of RBBR increased from 25 to 300 mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…A similar case was observed in methyl chloride adsorption by AC. 48 Rate constants from both PFO and PSO were found to decrease from 0.0215 to 0.0122 min −1 and from 0.00094 to 0.00004 g mg −1 min −1 , respectively, as the initial concentration of RBBR increased from 25 to 300 mg/L. At higher concentrations, competition among RBBR molecules for active sites makes the adsorption process slower, thus producing a smaller rate constant.…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…Molecular sieves are considered more efficient than other desiccants such as activated charcoal, silica gel, and alumina for dehydration in that they are small-pore adsorbents and with less possibility of co-adsorption of hydrocarbons [36]. Lad and Makkawi [37], after comparing the adsorption efficiency of methyl chloride among activated carbon, silica, and molecular sieves, found that the adsorption capability increased with the increase in adsorbent surface area. The molecular sieves vibrated by rotary shaking were The water-removal efficiency, as defined in Equation ( 1), was found to decrease with the operating time due to the broken structure and thus partial water-adsorption function loss of the molecular sieves after 3 h of absorbing water from ethanol accompanied by electromagnetic stirring in Figure 4.…”
Section: Effect Of Vibration Modes On Water-removal Efficiencymentioning
confidence: 99%
“…A number of studies have been reported by various authors for dye adsorption by using several adsorbents. Animal or plant-based activated charcoal such as rice husk, 16 coir pith, 17 bamboo, 18 sawdust, 19 agricultural wastes, 20 wood, 21 collagen, 22 bone, 23 and petroleum pitch, 24 inorganic adsorbents namely lignite, 25 zeolite, 26 and silica molecular sieves, 27 biopolymers, 28 and nano metal oxides [29][30][31][32][33] are the widely studied adsorbent materials. Carbon nanotubes (CNTs) possess unique structures and physical properties which makes them a promising candidate for the adsorption of dyes from industrial effluents.…”
Section: Introductionmentioning
confidence: 99%